Optimization of HCCI (Homogeneous Charge Compression Ignition) engine combustion chamber walls temperature to achieve optimum IMEP using LHS and Nelder Mead algorithm. (15th January 2017) - Mansoury, M.; Jafarmadar, S.; Talei, M.; Lashkarpour, S.M.
Abstract: Homogeneous Charge Compression Ignition (HCCI) engines produce power by using of auto ignition mechanism. In comparison to other conventional engines these types of engines have better efficiency and less pollution. Since, the temperature of combustion chamber walls is one of the important parameters for auto ignition and combustion characters; this work firstly, simulated multi-dimensional combustion in HCCI engines with Iso-butane as fuel by using of detailed kinetic chemical mechanism. After validating of results by existent experimental data, optimization of three parameters namely temperature of walls of piston, liner and head by means of Latin Hypercube Sampling method (LHS) and Nelder-Mead optimization algorithm was performed to reach to the maximum Indicated mean effective pressure (Imep). Finally, with comparison of effective parameters of optimized engine to those of original engine, it was found that by keeping the other operational parameters of engine such as fuel consumption at a fixed value, quantity of Imep has increased by 8.2%. Highlights: Root mean square error equal 0.014. The R 2 = 0.993 suggests the high level of confidence on the correlation results. The amount of Imep is 8.2% more than that in original state. Fuel consumption was considered fixed in optimization process. The optimum quantity of maximum pressure increased by 10.3%.